Kepemimpinan Transformasional dan Instruksional Kepala Sekolah dalam Implementasi Kurikulum Merdeka di SMA Al-Hidayah - Siregar, Riska Khairani; Hadijaya, Yusuf (Jurnal Pendidikan Madrasah, 2026)
The implementation of the Merdeka Curriculum in Indonesia requires adaptive, collaborative, and transformative school leadership to ensure sustainable educational change. However, many schools continue to experience challenges related to teacher readiness, instructional supervision, technological adaptation, and school culture transformation. This study aims to analyze the transformational and instructional leadership roles of school principals in supporting curriculum transformation at SMA Al-Hidayah. The research employed a qualitative case study approach involving the principal, vice principal, teachers, and educational staff as research informants selected purposively. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña involving data condensation, data display, and conclusion drawing. The findings reveal that the principal implemented transformational and instructional leadership simultaneously through teacher professional development programs, academic supervision, collaborative communication, and digital learning facilitation. The study also found that collaborative school culture, leadership commitment, and teacher motivation became major supporting factors, while technological limitations, economic constraints of students, and limited instructional time emerged as inhibiting factors. This research contributes to strengthening the discourse on adaptive educational leadership in the implementation of the Merdeka Curriculum, particularly in private senior high school contexts.